Development of hepatocellular adenomas and carcinomas in mice with liver-specific G6Pase-α deficiency - Roberta Resaz; Cristina Vanni; Daniela Segalerba; Angela R. Sementa; Luca Mastracci; Federica Grillo; Daniele Murgia; Maria Carla Bosco; Janice Y. Chou; Ottavia Barbieri; Luigi Varesio; Alessandra Eva (The Company of Biologists, 2014)
Glycogen storage disease type 1a (GSD-1a) is caused by a deficiency in glucose-6-phosphatase-α (G6Pase-α), and is characterized by impaired glucose homeostasis and a high risk of developing hepatocellular adenomas (HCAs). A globally G6Pase-α-deficient (G6pc−/−) mouse model that shows pathological features similar to those of humans with GSD-1a has been developed. These mice show a very severe phenotype of disturbed glucose homeostasis and rarely live beyond weaning. We generated liver-specific G6Pase-α-deficient (LS‑G6pc−/−) mice as an alternative animal model for studying the long-term pathophysiology of the liver and the potential treatment strategies, such as cell therapy. LS‑G6pc−/− mice were viable and exhibited normal glucose profiles in the fed state, but showed significantly lower blood glucose levels than their control littermates after 6 hours of fasting. LS‑G6pc−/− mice developed hepatomegaly with glycogen accumulation and hepatic steatosis, and progressive hepatic degeneration. Ninety percent of the mice analyzed developed amyloidosis by 12 months of age. Finally, 25% of the mice sacrificed at age 10-20 months showed the presence of multiple HCAs and in one case late development of hepatocellular carcinoma (HCC). In conclusion, LS‑G6pc−/− mice manifest hepatic symptoms similar to those of human GSD-1a and, therefore, represent a valid model to evaluate long-term liver pathogenesis of GSD-1a.